2013
DOI: 10.1097/aln.0b013e3182a2a243
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Patch (5%) in Treatment of Persistent Inguinal Postherniorrhaphy Pain

Abstract: Background: Evidence-based pharmacological treatment options for patients with persistent inguinal postherniorrhaphy pain are lacking. Methods: Twenty-one male patients, with severe, unilateral, persistent inguinal postherniorrhaphy pain, participated in a randomized, double-blind, placebo-controlled crossover trial, receiving lidocaine patch (5%) and placebo patch treatments in periods of 14 days separated by a 14-day wash-out period. Pain intensities (at rest, during movement, and pressure evoked [Numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…This is in line with results from recent studies on topical lidocaine that showed a tendency toward better effect of this topical sodium channel blocker in patients with preserved cold or thermal sensation [6,19]. Recently, a trial in painful diabetic neuropathy found that patients who showed a pain response to a topical capsaicin challenge also had slightly better pain relief following topical clonidine, which blocks a 2 -adrenergic receptors, although part of this difference seemed to be explained by a difference in placebo response [8].…”
Section: Sensory Pattern From Qst and Symptoms As Predictor Of Responsesupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with results from recent studies on topical lidocaine that showed a tendency toward better effect of this topical sodium channel blocker in patients with preserved cold or thermal sensation [6,19]. Recently, a trial in painful diabetic neuropathy found that patients who showed a pain response to a topical capsaicin challenge also had slightly better pain relief following topical clonidine, which blocks a 2 -adrenergic receptors, although part of this difference seemed to be explained by a difference in placebo response [8].…”
Section: Sensory Pattern From Qst and Symptoms As Predictor Of Responsesupporting
confidence: 92%
“…Numbers needed to treat (NNT) for more than 50% pain relief was 7.0 (95% CI 4. in the total population, 3.9 (95% CI 2. [3][4][5][6][7][8][9][10][11][12] in the IN, and 13 (95% CI 5.2-1) in the NIN group. Pain relief as measured by the specific scale was significantly better for oxcarbazepine compared with placebo in the total group (0.9 point, P < 0.001), but with no significant phenotype treatment interaction (0.3 point, P = 0.21).…”
Section: Effect On Pain Symptoms and Evoked Painmentioning
confidence: 96%
“…Eleven trials including data from 324 participants assessed the effectiveness of local anaesthetics in providing pain relief after inguinal hernia repair, spinal surgery, amputation and breast cancer surgery. Risk of bias was evident in three studies, and concerned incomplete outcome data, random sequence generation and blinding, and early trial termination.…”
Section: Resultsmentioning
confidence: 99%
“…Prospective, observational study in trauma patients with LNP of >3 months’ duration196.7 (NRS)1/2 plaster in one patient, 1/4 plaster in 18 patientsMean duration 19.5 weeksMean pain intensity decreased to 2.8 (reduction of 58.2%). Mean painful area decreased from 17.8 to 2.1 cm 2 (reduction of 87.6%)Bischoff et al [84]. Randomized, double-blind, placebo-controlled crossover trial216 at rest, 7 during movement, 8 during palpation (NRS)114 days with either lidocaine or placebo plaster/14-day washout period/14 days with alternative plasterChanges in pain intensity following treatment with lidocaine or placebo (summed pain intensity differences—SPID) were not significantly differentLikar et al [85].…”
Section: Supporting Evidence In the Treatment Of Lnpmentioning
confidence: 99%
“…Clinical Global Impression of Change (CGIC) scores of ‘Much Improvement’ or ‘Very Much Improvement’ were recorded for 76% of the patients (Table 2), including all the patients (17%) who had received the plaster as monotherapy [83]. However, lidocaine plasters did not reduce combined resting and dynamic pain ratings in 21 patients with severe, persistent inguinal postherniorrhaphy pain compared with placebo [84]. …”
Section: Supporting Evidence In the Treatment Of Lnpmentioning
confidence: 99%